Extraction and recovery of precursor chemicals from sugarcane bagasse, bamboo and triticale bran using conventional, advanced and fractionation pretreatment technologies - Diedericks, Danie (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.